2017
DOI: 10.1121/1.4982042
|View full text |Cite
|
Sign up to set email alerts
|

Horseshoe bats and Old World leaf-nosed bats have two discrete types of pinna motions

Abstract: Horseshoe bats (Rhinolophidae) and the related Old World leaf-nosed bats (Hipposideridae) both show conspicuous pinna motions as part of their biosonar behaviors. In the current work, the kinematics of these motions in one species from each family (Rhinolophus ferrumequinum and Hipposideros armiger) has been analyzed quantitatively using three-dimensional tracking of landmarks placed on the pinna. The pinna motions that were observed in both species fell into two categories: In "rigid rotations" motions the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…biosonar | ear motions | Doppler shifts | time-frequency signatures | nonlinear sensing C onspicuous pinna motions (1)(2)(3)(4)(5) are an integral part of biosonar behaviors in horseshoe bats and Old World leafnosed bats [families Rhinolophidae and Hipposideridae (6,7)]. These motions have been demonstrated to enhance sensing and navigation performance (8-10), but the functional role of these dynamic features and the underlying mechanisms have yet to be fully understood (7).…”
mentioning
confidence: 99%
“…biosonar | ear motions | Doppler shifts | time-frequency signatures | nonlinear sensing C onspicuous pinna motions (1)(2)(3)(4)(5) are an integral part of biosonar behaviors in horseshoe bats and Old World leafnosed bats [families Rhinolophidae and Hipposideridae (6,7)]. These motions have been demonstrated to enhance sensing and navigation performance (8-10), but the functional role of these dynamic features and the underlying mechanisms have yet to be fully understood (7).…”
mentioning
confidence: 99%
“…to alternate between rigid and non rigid motions [107] and have been shown to possess a large range of variability at least in the rigid motions [108]. Hence, it may be hypothesized that this variability provides a substrate for adaptation that would allow the animals to encode more useful sensory information.…”
Section: Discussionmentioning
confidence: 99%
“…3), based on the maximum changes in the distances between all five landmark points during the motion. If the maximum change was less than 2 mm, the motion was classified as rigid, else it was classified as non-rigid (Yin et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Numerical and physical methods indicate that noseleaf motions should impact the distribution of the emitted energy over direction (beam patterns) (He et al, 2015;Gupta et al, 2015;Fu et al, 2016). Rhinolophids and hipposiderids execute rigid and non-rigid pinna motions (Yin et al, 2017) accomplished by highly differentiated ear musculature (Schneider and Möhres, 1960). Experiments with robotic models have demonstrated target direction clues generated by rigid motions (Walker et al, 1998), and numerical predictions have shown changes in the nature of the beam patterns in response to non-rigid pinna motions (Gao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%